A systematic review of the South African work on the well-being of young people (2000–2016). (March 2019) - Govender, Kaymarlin; Bhana, Arvin; McMurray, Kerryn; Kelly, Jane; Theron, Linda; Meyer-Weitz, Anna; Ward, Catherine L; Tomlinson, Mark
Burgeoning research on the well-being of young people in recent years has made it difficult to identify conceptual gaps in the literature. We conducted a review of South African research in this area to better understand the use and measurement of the construct, as well as factors associated with it. The search of multiple databases identified 28 studies published in academic journals between 2000 and 2016. Within this period, studies that referred to well-being and its related subjective components varied significantly in terms of how they defined and operationalised these constructs, resulting in a fragmented body of work. The review highlights the need for a coherent research agenda in this area given the centrality of well-being research in promoting optimal outcomes in young people. Recommendations for strengthening South African research in this area are provided.